2020
DOI: 10.3390/cells9061494
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps in Periodontitis

Abstract: Neutrophils are key cells of the immune system and have a decisive role in fighting foreign pathogens in infectious diseases. Neutrophil extracellular traps (NETs) consist of a mesh of DNA enclosing antimicrobial peptides and histones that are released into extracellular space following neutrophil response to a wide range of stimuli, such as pathogens, host-derived mediators and drugs. Neutrophils can remain functional after NET formation and are important for periodontal homeostasis. Periodontitis is an infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 104 publications
1
48
1
4
Order By: Relevance
“…Next, Estúa-Acosta et al challenge the idea that the eye is an immune-privileged organ and provide evidence of NETs and their implication in pathophysiology in infectious keratitis, the leading cause of monocular blindness as well as non-infectious eye diseases [ 9 ]. Meanwhile, Magán-Fernández et al summarize the current knowledge about the role of NETs in the pathogenesis of periodontitis [ 10 ]. Infection of the periodontium starts with the accumulation of a complex bacterial biofilm that induces dysbiosis between the gingival microbiome and the immune response of the host, which involves impaired NET formation and/or elimination [ 10 ].…”
Section: Neutrophils and Nets In Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Estúa-Acosta et al challenge the idea that the eye is an immune-privileged organ and provide evidence of NETs and their implication in pathophysiology in infectious keratitis, the leading cause of monocular blindness as well as non-infectious eye diseases [ 9 ]. Meanwhile, Magán-Fernández et al summarize the current knowledge about the role of NETs in the pathogenesis of periodontitis [ 10 ]. Infection of the periodontium starts with the accumulation of a complex bacterial biofilm that induces dysbiosis between the gingival microbiome and the immune response of the host, which involves impaired NET formation and/or elimination [ 10 ].…”
Section: Neutrophils and Nets In Infectionmentioning
confidence: 99%
“…Meanwhile, Magán-Fernández et al summarize the current knowledge about the role of NETs in the pathogenesis of periodontitis [ 10 ]. Infection of the periodontium starts with the accumulation of a complex bacterial biofilm that induces dysbiosis between the gingival microbiome and the immune response of the host, which involves impaired NET formation and/or elimination [ 10 ]. Furthermore, the formation of biofilms promotes the efficient growth of pathogenic bacteria and fungi by providing optimal local environmental conditions and increased protection against the immune system [ 11 ].…”
Section: Neutrophils and Nets In Infectionmentioning
confidence: 99%
“…However, a study showed that aggregated NETs could resolve inflammation by the proteolysis of cytokines and chemokines ( Hahn et al., 2019 ). Current evidence also suggests that NETs contribute to many diseases like thrombosis ( Kimball et al., 2016 ), atherosclerosis ( Franck et al., 2018 ), autoimmune diseases ( Frangou et al., 2019a ; Frangou et al., 2019b ), sepsis ( Denning et al., 2019 ), and periodontitis ( Magan-Fernandez et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils in periodontitis also have a higher cytokine reactivity as the expression of chemokines and the release of cytokines (IL-1b, IL-6, IL-8, and TNF-a) are higher in neutrophils isolated from late-onset periodontitis patients (Lakschevitz et al, 2013;Ling et al, 2015). However, during periodontitis, the immune response is a double-edged sword because the cytokines and antimicrobial components produced during the immune response, such as IL-17, IL-6, IL-1b, TNF-a, ROS, and NETs, can induce bone resorption and soft tissue injury (Ramadan et al, 2020;Magan-Fernandez et al, 2020). In periodontitis, neutrophils are recruited through tethering and rolling, adhesion, crawling, and transmigration.…”
Section: Introductionmentioning
confidence: 99%